Alprostadil infusion in patients with dry age related macular degeneration: a randomized controlled clinical trial - Augustin, Albert J.; Diehm, Curt; Grieger, Frank; Bentz, Juergen (Expert opinion on investigational drugs, 2013)
Background: Age-related macular degeneration is the leading cause of blindness among elderly individuals in industrialized countries. New drugs and advanced concepts for the treatment of dry AMD (dAMD) are needed. A new approach is the application of intravenous infusions of prostaglandin E1. Objective: The aim of this study was to assess efficacy and safety of intravenous alprostadil infusion in patients with dAMD. Methods: This was a prospective, randomized, multi-center study. Patients were treated with intravenous infusion of either 60 µg alprostadil or placebo over 3 weeks. Main efficacy outcomes were mean differences in best corrected visual acuity (BCVA) from baseline assessed in early treatment diabetic retinopathy study (ETDRS) lines immediately, 3 months and 6 months after treatment. Results: In the full analysis set (FAS) a mean difference of 0.89 ± 0.537 ETDRS lines according to analysis of variance-covariance (ANCOVA) resulted in the alprostadil group (n = 16) and a mean difference of -0.05 ± 0.578 in the placebo group (n = 17) 3 months after end of treatment. Thus, effectiveness of alprostadil infusion was numerically superior to placebo treatment by a mean of 0.94 lines after 3 months (1.51 lines after 6 months). These findings were more pronounced in the per protocol set (PPS). Safety results were in line with the good safety profile of alprostadil. Conclusion: A numerical treatment effect in favor of alprostadil was visible, which lasted until the end of follow up. These results provide further evidence that alprostadil probably has a therapeutic effect in the treatment of dAMD and justify further clinical studies.
Gesehen am 22.10.2020